Digestive Discomforts and Effect of Ingested Food in People Performing Hajj - Osama A. Shaikh-Omar; Eslam A. Header; Hassan M. Bukhari (Journal of Basic & Applied Sciences, 2021)
A variety of health issues have been investigated in the Hajj pilgrims (HPs) in KSA. However, it is still obscure to decide which meals contribute to health related issues specifically gastrointestinal disorders and allergies. Hence present study was planned to compare the effect of using different meals on GIT disorders and allergies. The data was categorized into two groups. Group 1 of age matched HPs comprised a Functional Digestive System Questionnaire (FDSQ) to study digestive disorders. Group 2 HPs were compared for those received Toafa Corporation Meals (TCM) and those did not received Toafa Corporation Meals (NTCM). The FDSQ showed some of the gastrointestinal symptoms in male and female Hajj pilgrims differing significantly (p<0.05). The efficacy of the treatment was evaluated by subject recovery scoring (SRS). The 61.7% HPs taking TCM revealed various discomforts and food allergy and the 50.6% HPs using NTCM did not suffer from any disorders. However, the pilgrims taking the meals provided by the Toafa corporation but not showing allergy were more significant in number (p=0.0002). The existing study presents a new method (construction of a FDSQ) for comparing gastrointestinal and other disorders. The present study recommends that Toafa Corporation should provide suitable meals for thepilgrims to meet their actual needs during Hajj and health situation.